2020
DOI: 10.1007/s10055-020-00487-x
|View full text |Cite
|
Sign up to set email alerts
|

Immersive training of first responder squad leaders in untethered virtual reality

Abstract: We present the VROnSite platform that supports immersive training of first responder units’ on-site squad leaders. Our training platform is fully immersive, entirely untethered to ease use and provides two means of navigation—abstract and natural walking—to simulate stress and exhaustion, two important factors for decision making. With the platform’s capabilities, we close a gap in prior art for first responder training. Our research is closely interlocked with stakeholders from multiple fire brigades to gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…This quasi-experiment sought to understand if a VR environment could elicit a similar acute stress response as a realistic SBT exercise related to law enforcement active shooter response training. With more first responder training utilizing VR systems (Mossel et al, 2021; Peretti et al, 2021), it’s important to understand if such training is comparable to SBT in provoking stress. Both difference-in-differences and two-way ANOVA analyses indicate that VR technology can elicit a similar acute stress response as a short (∼50 seconds) SBT utilizing professional actors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This quasi-experiment sought to understand if a VR environment could elicit a similar acute stress response as a realistic SBT exercise related to law enforcement active shooter response training. With more first responder training utilizing VR systems (Mossel et al, 2021; Peretti et al, 2021), it’s important to understand if such training is comparable to SBT in provoking stress. Both difference-in-differences and two-way ANOVA analyses indicate that VR technology can elicit a similar acute stress response as a short (∼50 seconds) SBT utilizing professional actors.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have recently begun to suggest the use of VR as a medium to provide training to first responders (Mossel et al, 2021; Peretti et al, 2021). Although it has primarily been used for recreational gaming and entertainment, VR systems offer two unique benefits when used for training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[16] Corresponding ongoing and already completed research initiatives have addressed these improvement options, but the concrete application is currently still scarce. [7,9,14,[28][29][30][31] Further research revealed that there are initial uses of these technologies in the area of quality methods, e.g. with the Virtual Quality Toolbox (VQT) [32].…”
Section: Application Of Vr and Ar In Connection With Quality Methodsmentioning
confidence: 99%
“…[10 -12]The experience of time travel to historical events is exemplary [10,13], to name the free exploration of the universe and its planets and thus the overcoming of physical barriers. In addition, the limits of irreversible decisions in psychologically demanding dangerous situations, such as the training of fire brigades under realistic conditions, can be safely enabled [14,15]. With AR it is also possible to display additional content and information in the real environment, directly in the user's field of vision.…”
Section: Introductionmentioning
confidence: 99%
“…At present, much work has been conducted in this field. According to the hardware system used, these works can be divided into two main categories, namely, personal computer (PC)‐based 3D visualization of disaster scenes (Catulo, Falcão, Bento, & Ildefonso, 2018; Cheng, Chen, & Cao, 2019; Li, Li, Chen, Zheng, & Liu, 2018; Lu, Yang, Xu, & Xiong, 2020; Redweik, Teves‐Costa, Vilas‐Boas, & Santos, 2017; Winkler, Zischg, & Rauch, 2018; Wu et al., 2019; Zhi, Liao, Tian, Wang, & Chen, 2019) and PC virtual reality (VR)‐based 3D visualization of disaster scenes (Feng, González, Amor, et al., 2020; Feng, González, Trotter, et al., 2020; Fujimi & Fujimura, 2020; Jacquinod & Bonaccorsi, 2019; Lin, Cao, & Li, 2020; Mossel et al., 2021; Tibaldi et al., 2020; Wang, Hou, Miller, Brown, & Jiang, 2019). The 3D visualization of disaster scenes based on PC VR has a stronger sense of immersion and can give people a more immersive experience.…”
Section: Introductionmentioning
confidence: 99%